(untitled) (Research, Society and Development, 2022)
Objective: the objective of this study was to analyze the prevalence of children and adolescents in the North region and Palmas, capital of Tocantins. Methodology: the method used was the integrative literature review, consisting of the search for scientific and official articles from databases International library of Medicine National Institutes of Health (PubMed), virtual health library (VHL research), Scientific Electronic Library Online (SCIELO) and Google Axel. Data are derived from dental caries indices (dmft - decayed deciduous teeth, lost due to caries and filled and DMFT - permanent decayed teeth, lost to decay and filled) obtained in epidemiological surveys carried out in Brazil in 1986, 1996, 2003 and 2010. Results: although epidemiological surveys have registered a reduction in the prevalence of dental caries in developed countries over the years and Brazil follows this global trend, childhood is still a public health problem. The study that the rate of dental caries in Palmas is higher in children than in adolescents. The percentage of restorative teeth, component “o” of the dmft index, is lower in five-year-old children in the capital. The study showed that tooth decay disproportionately affects the underprivileged population, remaining over the years marked differences in the prevalence of caries between and across the country. Few data were found in the literature referring to the State of Tocantins and Palmas. Conclusion: it is concluded that oral health promotion and prevention actions were prevented until unintentional childhood at early ages in a way with the municipality of prevalence in oral age.